1984
DOI: 10.1097/00000658-198411000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis Near Its Centenary

Abstract: In an analysis of the first 72 cases treated after the formulation of the appendicitis syndrome in 1886 compared with the experience from 1929-1959 and with 307 randomly selected recent cases, the major therapeutic trend has been an emphasis on appendectomy before perforation and abscess formation occur. The rate of infection nonetheless remains approximately 17%. Although the overall mortality rate has declined from 26% overall (40% for surgery) to 0.8%, the current rate of perforation is 28%, with a diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
154
3
18

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(192 citation statements)
references
References 44 publications
17
154
3
18
Order By: Relevance
“…Embora os índices de mortalidade atribuídos à apendicite terem diminuído acentuadamente no último século, as suas complicações continuam comuns 6 . Isto é atribuído ao fato das perfurações manterem-se freqüentes (17 a 20%) a despeito do aumento do uso dos métodos diagnósticos de ima- gens como a ultra-sonografia e a tomografia computadorizada, (2).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Embora os índices de mortalidade atribuídos à apendicite terem diminuído acentuadamente no último século, as suas complicações continuam comuns 6 . Isto é atribuído ao fato das perfurações manterem-se freqüentes (17 a 20%) a despeito do aumento do uso dos métodos diagnósticos de ima- gens como a ultra-sonografia e a tomografia computadorizada, (2).…”
Section: Discussionunclassified
“…Houve uma dramática redução na mortalidade associada à apendicite aguda nos últimos 50 anos, de aproximadamente 26% para menos de 1% 6 . Entretanto, a morbidade não apresentou queda semelhante 6,7,8 , principalmente pela alta incidência de perfurações ainda existentes (17 a 20%), mesmo após o desenvolvimento dos métodos de diagnóstico por imagem 1,9 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Overall, a negative appendicectomy rate of approximately 20% is commonly reported [2][3][4][5][6][7][8][9]. Nowadays commonly used diagnostic aids for appendicitis are CECT abdomen, laparoscopy, diagnostic scores, USG.…”
Section: Introductionmentioning
confidence: 99%
“…4 Despite the tendency to late diagnosis of acute appendicitis during pregnancy, it is reported up to 23% of negative appendectomy rate. 5 However, a recent study reported that higher rates of adverse obstetric outcomes were observed amongst pregnant women with negative appendectomy. 6 Ultrasonography (USG) is a non-invasive and inexpensive test, which does not expose the patient to radiation, and is reported to have sensitivity and specificity of 86 and 81% for the diagnosis of acute appendicitis, respectively.…”
Section: Introductionmentioning
confidence: 99%